The genera and species of Comatulidae (Comatulida: Crinoidea): taxonomic revisions and a molecular and morphological guide - Summers, Mindi M.; Messing, Charles G.; Rouse, Greg W. (Zootaxa, 2017)
We provide a guide for identification of Comatulidae, a family of crinoid echinoderms, incorporating morphological and molecular evidence. A non-dichotomous key for all genera is included, as well as photographs of species most likely to be encountered in the tropical western Pacific Ocean. Based on sequencing of cytochrome oxidase subunit I (COI), and other genes when necessary, we identified four cases where taxonomic revision was needed. We synonymized Comaster nobilis under Comaster schlegelii, and Clarkcomanthus exilis under Clarkcomanthus comanthipinnus, and re-described Clarkcomanthus albinotus. We also showed the variation of COI sequences within and among species, which varies from lineage to lineage. In some cases, specimens with obvious morphological disparity possessed very little intraspecific molecular diversity (<1%). In others, specimens with nearly identical external appearances exhibited quite divergent COI sequences (up to 6%). These results, combined with the non-dichotomous key herein, offer guidelines for identification and discussion of existing and new species of Comatulidae.